REPRESENTATION OF SOCIAL EDUCATION VALUE OF TRANSGENDER CHARACTER IN THE NOVEL OF CALABAI BY PEPI AL-BAYQUNIE AS STIMULUS OF CHARACTER BUILDING IN PROSE APPRECIATION LEARNING IN STKIP PONOROGO - Aji Kusuma, Krisna; J. Waluyo, Herman; EKo Wardani, Nugraheni (Journal of Education Research and Evaluation, 2018)
This research is a qualitative descriptive research that aimed to understand the life of the transgender figure in the novel of Calabai, analyzing the values of social education reflected through the example of calabai attitude, and analyzing the integration of social education values of calabai figures as a stimulus to build character in learning of prose appreciation in STKIP PGRI Ponorogo. The source of data used in this research is Calabai novel document by Pepi Al-Bayqunie, while the data collected in the form of the result of the study note of the novel. Data collecting technique uses non-interactive technique by doing intensive reading on the novel and do recording actively by content analyzing method. Validity of this research uses data triangulation technique and method of triangulation. Data analysis techniques using interactive analysis model, which is data reduction, presentation, and conclusion. The results of this research show that the sensitivity and the concern of transgender characters in the novel of Calabai to fellows is a representative value of social education model to the younger generation. The value of social education reflected through the transgender figure in the novel of Calabai includes the social attitude of caring family, caring friend, and caring for the community. Social care is manifested in the form of obedience, patience, sacrifice, sincerity, religious, sympathy and empathy, gratitude, and compassion. The values of social education represented by transgender figures in the novel Calabai can be used as a stimulus to build character in prose appreciation learning in STKIP PGRI Ponorogo.